2023
DOI: 10.3390/ani13233701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rumen Fermentation Characteristics on Stress-Related Hormones and Behavior in Sheep

Qianrige,
Sanggun Roh,
Da-Hye Kim
et al.

Abstract: This study investigated the relationship between rumen fermentation, stress-related hormones, and behavior in sheep with the aim of providing insights for improving animal welfare and feed management practices. Eight lambs were assigned to either a high concentration or control group. Blood samples were collected for hormone analysis, and an open field test was conducted to observe behavioral stress responses. The results showed that diet composition may affect the behavior of ruminants in response to stressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…It has been reported that excessive intake of roughage with a high fiber content will increase the acetic acid content in the rumen [30,31]. A large amount of acetic acid produced by rumen fermentation in sheep is oxidized through the tricarboxylic acid cycle for energy supply or used for fatty acid synthesis to maintain energy intake in winter [32,33]. Acetic acid and propionic acid are the main sources of energy for the rumen papillae, and they produce ATP through oxidation for use by the rumen papillae and other cells.…”
Section: Differences In Volatile Fatty Acids In the Rumen Contents Of...mentioning
confidence: 99%
“…It has been reported that excessive intake of roughage with a high fiber content will increase the acetic acid content in the rumen [30,31]. A large amount of acetic acid produced by rumen fermentation in sheep is oxidized through the tricarboxylic acid cycle for energy supply or used for fatty acid synthesis to maintain energy intake in winter [32,33]. Acetic acid and propionic acid are the main sources of energy for the rumen papillae, and they produce ATP through oxidation for use by the rumen papillae and other cells.…”
Section: Differences In Volatile Fatty Acids In the Rumen Contents Of...mentioning
confidence: 99%